Opioids and adjuvant analgesics in current treating of pain - Stepanović-Petrović Radica; Tomić Maja (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2019)
Morphine, as a paradigm of opioids, is 'gold standard' in treating severe pain, to which all other drugs are compared. However, abuse and respiratory depression potentials have resulted in 'opiophobia' among health professionals, and underutilization of opioids as analgesics. But, addiction and respiratory depression are almost never present in pain managenent in palliative care. So, fear of addiction and respiratory depression should not prevent increasing of opioid dose in those patients in paliative care who still suffer of severe pain. Opioids are ineffective in treating neuropathic pain. Antiepileptics (carbamazepine, pregabalin, gabapentin) and antidepressants (amitriptyline, duloxetine) are used for neuropathic pain.